Respiration rates and microbiological development in yellow-dent maize seeds stored between 12% and 14% moisture content - Abadia, María Bernadette; Castellari, Claudia; Monterubbianesi, María Cecilia; Bartosik, Ricardo Enrique (Elsevier, 2024)
Understanding microbial development under the typical storage conditions of maize seeds is crucial for maintaining seed quality and ensuring successful crop establishment. In this study, the respiration and microbial growth of yellow-dent maize seeds stored at 12%, 13%, and 14% moisture content (corresponding to 65%, 70%, and 75% relative humidity, respectively) and 25 °C were investigated. Two maize seed lots (hybrids KM4500 and KM4580) with different initial fungal loads were used in the experiments. To calculate the respiration rates, seeds were stored in hermetically closed jars and the oxygen and carbon dioxide concentrations were monitored for 180 days. The microbial load (colony forming units and percentage of infected seeds) was measured prior and after storage at the three humidity levels. At 65% and 70% relative humidity, respiration rates were close to zero in both seed lots, indicating minimal microbial activity. However, at 75% relative humidity, respiration rates showed a bell-shaped pattern, suggesting the onset of microbial activity in both seed lots. The seed lot with higher initial fungal load (KM4500) presented a higher respiration rate. The microbial load decreased at 65% and 70% relative humidity and the decreasing trend reverted at 75% relative humidity. This work indicates that 70% relative humidity is a safe storage moisture to prevent microbial activity at 25 °C in the studied yellow-dent maize seeds, independently of their initial fungal load. Hermetic storage, also, would make sense for seed storage only above 75% r.h. (14% m.c.) This study provides valuable insight for preserving seed quality during long-term commercial storage